2005
DOI: 10.1111/j.1479-828x.2005.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenting symptoms of epithelial ovarian cancer

Abstract: Patients with early stage ovarian cancer are likely to be younger and to have larger, better differentiated tumours that are more often non-serous histologically. Advanced disease is not invariably due to delayed diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 13 publications
4
55
0
1
Order By: Relevance
“…There have been several studies refuting the suggestion that delay in diagnosis is responsible for the advanced disease. 2,13,17,18 In these studies, women with early stage disease reported similar or rather longer duration of symptoms, indicating there may be significant biological differences between the early and advanced stages. Nevertheless, Goff's symptom index is meaningful in that it made patients and clinicians aware of specific symptoms as early alarm.…”
Section: 10mentioning
confidence: 86%
“…There have been several studies refuting the suggestion that delay in diagnosis is responsible for the advanced disease. 2,13,17,18 In these studies, women with early stage disease reported similar or rather longer duration of symptoms, indicating there may be significant biological differences between the early and advanced stages. Nevertheless, Goff's symptom index is meaningful in that it made patients and clinicians aware of specific symptoms as early alarm.…”
Section: 10mentioning
confidence: 86%
“…The symptoms are often very insidious and the duration of symptoms not very different between patients with early stage or advanced stage disease [13,14]. This may reflect the different biological behavior of the various histological subtypes; for example, grade 1 serous, clear cell, mucinous, and endometrioid cancers are commonly early stage at presentation, whereas high-grade serous cancers are most often Stage III because of early dissemination by a more aggressive cancer.…”
Section: Diagnosismentioning
confidence: 99%
“…Presenting symptoms include vague abdominal pain or discomfort, menstrual irregularities, and dyspepsia and other mild digestive disturbances, which may have been present for only a few weeks [13,14,43]. As the disease progresses, abdominal distention and discomfort from ascites generally worsen, and may be associated with respiratory symptoms from increased intra-abdominal pressure or from the transudation of fluid into the pleural cavities.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…3 Izostanak simptomatologije u početnim stadijumima razvoja ovih tumora dovodi do toga da se dijagnoza bolesti postavlja relativno kasno, često tek kada se tumor nađe u uznapredovalom stadijumu, što posebnu važnost daje preciznom utvrđivanju patohistoloških prognostičkih faktora neoplazme. 4,5 Tu se pre svega misli na proliferativni potencijal tumora, izmenu sekrecije mucina i očuvanost transporta sekretornog imunoglobulina A. Proliferativna aktivnost neoplazmi je jedna od njihovih najvažnijih prognostičkih karakteristika. Danas je standard za procenu ove aktivnosti upotreba markera proliferacije poput Ki-67 koji, kada su u pitanju ovarijalni tumori prema Wang-u i sar.…”
unclassified